Building a Community of Superusers to Leverage a Collaboration Platform - Tunning, Maggie (World Bank, Washington, DC, 2012)
Social networking and collaboration platforms don't work without people. The most advanced technology won't achieve results without a devoted user base that creates and shares content. The World Bank's social collaboration platform 'Scoop' prioritizes relationships with users as part of the user adoption and engagement strategy. This smart lesson describes the original development of Scoop, its initial release for trial among a select group of 'Superusers,' and the ongoing refinement of its functionalities to meet the Bank's business needs. Lessons learned speak to the importance of bolstering the Superusers so they in turn can engage a broader community of users and turn them into champions for social collaboration.